Adsorption of hydrophobin/β-casein mixtures at the solid-liquid interface - Tucker, I; Petkov, J; Penfold, J; Thomas, R; Cox, A; Hedges, N (Elsevier, 2016)
The adsorption behaviour of mixtures of the proteins β-casein and hydrophobin at the hydrophilic solid-liquid surface have been studied by neutron reflectivity. The results of measurements from sequential adsorption and co-adsorption from solution are contrasted. The adsorption properties of protein mixtures are important for a wide range of applications. Because of competing factors the adsorption behaviour of protein mixtures at interfaces is often difficult to predict. This is particularly true for mixtures containing hydrophobin as hydrophobin possesses some unusual surface properties. At β-casein concentrations ⩾0.1wt% β-casein largely displaces a pre-adsorbed layer of hydrophobin at the interface, similar to that observed in hydrophobin-surfactant mixtures. In the composition and concentration range studied here for the co-adsorption of β-casein-hydrophobin mixtures the adsorption is dominated by the β-casein adsorption. The results provide an important insight into how the competitive adsorption in protein mixtures of hydrophobin and β-casein can impact upon the modification of solid surface properties and the potential for a wide range of colloid stabilisation applications.